2005
DOI: 10.3168/jds.s0022-0302(05)72677-1
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of Bovine Sodium/Glucose Cotransporters

Abstract: The Na+-dependent glucose cotransporters (SGLT) are a family of glucose transporters that mediate an active, sodium-linked transport process against an electrochemical gradient. The SGLT are known to play important roles in absorption of dietary D-glucose and D-galactose from the intestinal lumen and in the reabsorption of D-glucose from the glomerular filtrate in kidney. To study the role and regulation of SGLT in tissues of lactating cows, we cloned and sequenced the full-length cDNA of bovine SGLT1 and SGLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…- The members of the SGLT family also share considerable homology among the proteins (21-70% amino acid identity to SGLT1) and contain several conserved sodium:solute symporter family signatures that are characteristics of this family (GenBank accession numbers PS00456, PS00457 and PS50283). The SGLTs are predicted to have 14-15 transmembrane helices [3,16,17]. This second structural model is supported by experimental data of glycosylation studies, antibody tagging, mass spectrometry and other methods [3].…”
Section: Structural Characteristics Of Glut and Sglt Proteinsmentioning
confidence: 63%
See 2 more Smart Citations
“…- The members of the SGLT family also share considerable homology among the proteins (21-70% amino acid identity to SGLT1) and contain several conserved sodium:solute symporter family signatures that are characteristics of this family (GenBank accession numbers PS00456, PS00457 and PS50283). The SGLTs are predicted to have 14-15 transmembrane helices [3,16,17]. This second structural model is supported by experimental data of glycosylation studies, antibody tagging, mass spectrometry and other methods [3].…”
Section: Structural Characteristics Of Glut and Sglt Proteinsmentioning
confidence: 63%
“…It is predominantly expressed in the brush border membrane of mature enterocytes in the small intestine and plays a major role in absorption of dietary D-glucose and D-galactose from the intestinal lumen [81,82]. However, SGLT1 expression has been observed in many tissues in which glucose is believed to be taken up by the facilitative process, such as the mammary gland and liver [17]. It, thus, may be multifunctional, such as also functioning as a water cotransporter [83].…”
Section: Sglt1 (Slc5a1)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, many signalling pathways in the lactating pBMEC are known, i.e. the janus kinase/signal transducer and activator of transcription cascade (Darnell, 1997), the growth hormone effects in the mammary mammalian target of rapamycin signalling pathway (Cui et al, 2003), the interaction of insulin and the major milk protein transcription factor E74-like factor 5 (Menzies et al, 2009), and the amino acids and glucose transporters (Zhao et al, 1996(Zhao et al, , 2005. Future research in that field could provide valuable information on improved lactation performance of dairy cows.…”
Section: Milk Protein Gene Expressionmentioning
confidence: 99%
“…However; a lactating mammary gland cannot synthesize glucose from other precursors due to the absence of glucose-6-phosphatase (Threadgold and Kuhn 1979) and so is dependent on the blood supply for its glucose requirement. Mammary glucose uptake, which is performed by both active and passive transport processes (Zhao et al 1999(Zhao et al , 2005, is independent of the concentration of glucose and insulin in the arterial blood during lactation. It has also been suggested that the blood glucose concentration affects the rate of synthesis of milk lactose, hence milk volume by osmotic association (Kronfeld 1982).…”
Section: Introductionmentioning
confidence: 99%